Life cycle assessment of household biogas production in Egypt: Influence of digester volume, biogas leakages, and digestate valorization as biofertilizer. (1st March 2021) - Ioannou-Ttofa, Lida; Foteinis, Spyros; Seifelnasr Moustafa, Amira; Abdelsalam, Essam; Samer, Mohamed; Fatta-Kassinos, Despo
Abstract: Biogas production from animal manure can address many negative impacts of traditional energy generation and also improve living conditions in rural communities in Egypt, the case study herein, and further afield. Even though techno-economical aspects of the household biogas digester technology have been thoroughly studied, its environmental sustainability, especially under Egypt's conditions, remains largely unknown. To this end, life cycle inventory data were collected from typical fixed-dome digesters operating in Egypt. Environmental modelling was based on the life cycle assessment methodology using SimaPro. It was identified that the 100-year global warming potential for producing 1 m 3 of biogas under Egypt's conditions amounts to 2.72 kg CO2 eq., while its total environmental footprint was 160.1 mPt. The main contributor was the operational phase (89.1%), while the construction phase had a much smaller contribution (10.9%). The main environmental hotspots were identified as the manure required to drive the process, closely followed by biogas leakages and intentional releases. By minimizing biogas losses, the system's environmental sustainability largely improves (∼60% reduction) and could be on the same level with the one of larger biogas units operating in developing countries. Furthermore, it was identified that the digester volume plays an overall small role in the system's environmental performance; however, oversized digesters grossly affect the environmental sustainability, due to the large amounts of biogas intentional releases. Finally, the use of digestate as a biofertilizer appears to be environmentally sustainable (∼38% reduction of total environmental footprint). Taken together, the results obtained in this study provide substantial information for policy- and decision-making on renewable energy development in rural Egypt and beyond. Highlights: The environmental sustainability of Egyptian household digesters was investigated. The total environmental footprint for producing 1 m 3 of biogas under Egypt conditions was 160.1 mPt. Its main environmental hotspots were the manure, and the biogas leakages/intentional releases. Oversizing the digester volume grossly affects its environmental sustainability. The use of digestate as a biofertilizer appears to be environmentally sustainable.